ANALISIS DETERMINAN FAKTOR-FAKTOR YANG MEMPENGARUHI NIAT PENGGUNAAN SOFTWARE AUDIT - T Husain (Jurnal Ilmiah Matrik, 2017)
This research aim to analyze determinant factors influence of intetion to audit software usage i.e. perceived benefits, adoption risk, organizational readiness and external pressure with technologi model acceptance (TAM) which is constucted by adding demographic characteristics factor i.e. age, expertise, and past adoption experience as a moderationg variable.The population in this research are individuals who work as auditors and dwelling place on district of DKI Jakarta. Sampling technique using purposive method, with sample quotation of 115 respondents. The data analysis method using moderated structural equation modeling (MSEM) techniques, with the validity testing and instrument reliability, goodness-of-fit model and hypothesis testing. The results of this research showed that 79,13% have using audit software. Intention to audit software is only influenced by the organizational readiness factors whereas the perceived benefits, adoption risk and external pressure have no significant effect. Overall, demographic characteristics had no moderate impacts of perceived benefits and adoption risk toward intention to audit software.